Assessing factors associated with FSM practices among residents living in Baidoa, Somalia - Hussein, Mohamud Mohamed; Odongo, Alfred Owino; Kerochi, Atei; Snuggs, Jason (International Journal Of Community Medicine And Public Health, 2023)
<div id="chakra-toast-manager-bottom-right" style="position: fixed; z-index: var(--toast-z-index, 5500); pointer-events: none; display: flex; flex-direction: column; bottom: env(safe-area-inset-bottom, 0px); right: env(safe-area-inset-right, 0px);" role="region" aria-live="polite" aria-label="Notifications"> Background: Excreta is a normal part of life, but if it is not appropriately controlled, it can lead to waterborne diseases, most low- and middle-income countries lack adequate FS treatment and management service coverage. The study's main goal was to assess fecal sludge management practices and associated factors among communities in Baidoa, Somalia. Methods: The study adopted a cross-sectional study design. The collected data was analyzed using Statistical Software for Social Sciences (SPSS) version 21. Descriptive statistics and chi-square were used. Qualitative data was thematically analyzed. Results: The study identified that 66% of the Baidoa FS produced is not well managed. Regarding community perceptions, about 75.80% of the study participants don’t understand poor sanitation while 30.1% don’t know the relationship between poor sanitation and health risk. Results showed a significant association between education level and access to latrines, ( (4, n=385) = 50.672, p<0.001). The findings revealed a statistically significant association between residential status and access to FSM services ( (23, n=385) = 148.82, p<0.001). HH monthly income is significant in access to FSM services ( (64, n=385) = 113.180, p<0.001); and limited capacity of Baidoa municipality. Conclusions: There are gaps in FSM management and residents are at risk of health hazards/disease outbreaks. The key recommendation is the development of strategic sanitation service delivery planning in view of FSM service chain and formulation of regulations to govern FSM service provision by different actors to safeguard the health safety of living, learning, and working environments.